2018
DOI: 10.1121/1.5064956
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a near-end listening enhancement algorithm by combined speech intelligibility and listening effort measurements

Abstract: Previous studies showed that near-end listening enhancement (NELE) algorithms can significantly improve speech intelligibility in noisy environments. This study investigates the benefit of the NELE algorithm AdaptDRC in normal-hearing listeners at signal-to-noise ratios (SNRs) for which speech intelligibility is at ceiling, by evaluating listening effort for processed and unprocessed speech in the presence of speech-shaped and cafeteria noise. The results suggest that the NELE algorithm is able to reduce liste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Finally, the differences in the attenuations of the masks would be expected to influence listening effort, which is something that is not well measured by a metric such as the SII. 42,43 V. CONCLUSIONS A series of experiments have quantified the insertion losses from face masks and shields with clear plastic panels that allow speech-reading. These have then been related to the effects of speech perception through calculations of the SII.…”
Section: G Evaluation Using the Siimentioning
confidence: 99%
“…Finally, the differences in the attenuations of the masks would be expected to influence listening effort, which is something that is not well measured by a metric such as the SII. 42,43 V. CONCLUSIONS A series of experiments have quantified the insertion losses from face masks and shields with clear plastic panels that allow speech-reading. These have then been related to the effects of speech perception through calculations of the SII.…”
Section: G Evaluation Using the Siimentioning
confidence: 99%
“…Previous studies have shown that listening effort can vary with regard to the speech type [3,21] and masker type [22]. Rennies et al [3] concluded that listening effort and speech intelligibility are appropriate for assessing speech perception and algorithm performance at high SNRs and very low SNRs, respectively. We speculate that listeners choose the speech feature value with which they exert the least listening effort and maximizes their intelligibility.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that near-end listening enhancement algorithms can produce substantial intelligibility improvements in noisy conditions compared to unprocessed speech [1,2]. A new focus for speech modification techniques, over and above mere intelligibility, is to reduce listening effort [3]. One approach currently being investigated is to measure listening preference when intelligibility is at or near ceiling levels [4].…”
Section: Introductionmentioning
confidence: 99%
“…The Adapt- DRC algorithm aims at a compromise between intelligibility and speech naturalness; notwithstanding smaller EIC gains, this strategy might be better suited for long listening periods. A valuable extension to the present study would be a subjective evaluation of perceived quality / naturalness / listening comfort, as well as a subjective and objective measurement of the cognitive load caused by listening to modified speech in realistic noise [16].…”
Section: Discussionmentioning
confidence: 99%